A Pharmacokinetics‐Informed Approach to Navigating Hydroxychloroquine Shortages in Patients With Rheumatic Disease During the COVID‐19 Pandemic. Issue 8 (29th July 2020) - Scheetz, Marc H.; Konig, Maximilian F.; Robinson, Philip C.; Sparks, Jeffrey A.; Kim, Alfred H.J.
Abstract : Objective: The recent hydroxychloroquine (HCQ) shortage due to use in coronavirus disease 2019 (COVID‐19) has forced some rheumatic disease patients to choose between continuing their current dose of HCQ but exhaust their supply early or ration it in order to prolong its use. Blood HCQ concentrations are directly correlated with disease activity in rheumatic diseases such as systemic lupus erythematosus. We sought to model how changes in HCQ dosage will best maintain sufficient blood HCQ concentrations for the longest period of time in order to avoid potential future flares. Methods: A one‐compartment pharmacokinetic model was used to predict mean blood HCQ concentrations. Monte Carlo simulations with 10‐fold inflated model parameter variance was utilized to assess the impact of variability. Results: Maintenance of 400 mg/d resulted in mean therapeutic whole‐blood HCQ concentrations that exceeded 700 ng/ml for 10.5 days, whereas HCQ rationing by reducing the dose by half resulted in the mean concentration remaining above 700 ng/ml for 2.4 days (net gain = 8 days). Variability analysis demonstrates that results may differ at the individual level, dependent on baseline blood HCQ concentrations. Conclusion: Although mean blood concentrations exceed 700 ng/ml for a longer time if patients maintain their full dose of HCQ, more information is needed to fully understand the elimination of HCQ at the patient level, particularly the contribution of tissue stores of HCQ transiting back into the blood.